Deficiency of tumour necrosis factor-related apoptosis-inducing ligand exacerbates lung injury and fibrosis. Issue 9 (11th April 2012) - McGrath, Emmet E; Lawrie, Allan; Marriott, Helen M; Mercer, Paul; Cross, Simon S; Arnold, Nadine; Singleton, Vanessa; Thompson, Alfred A R; Walmsley, Sarah R; Renshaw, Stephen A; Sabroe, Ian; Chambers, Rachel C; et al.
Abstract : Background: The death receptor ligand tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) shows considerable clinical promise as a therapeutic agent. TRAIL induces leukocyte apoptosis, reducing acute inflammatory responses in the lung. It is not known whether TRAIL modifies chronic lung injury or whether TRAIL has a role in human idiopathic pulmonary fibrosis (IPF). We therefore explored the capacity of TRAIL to modify chronic inflammatory lung injury and studied TRAIL expression in patients with IPF. Methods: TRAIL −/− and wild-type mice were instilled with bleomycin and inflammation assessed at various time points by bronchoalveolar lavage and histology. Collagen deposition was measured by tissue hydroxyproline content. TRAIL expression in human IPF lung samples was assessed by immunohistochemistry and peripheral blood TRAIL measured by ELISA. Results: TRAIL −/− mice had an exaggerated delayed inflammatory response to bleomycin, with increased neutrophil numbers (mean 3.19±0.8 wild type vs 11.5±5.4×10 4 TRAIL −/−, p<0.0001), reduced neutrophil apoptosis (5.42±1.6% wild type vs 2.47±0.5% TRAIL −/−, p=0.0003) and increased collagen (3.45±0.2 wild type vs 5.8±1.3 mg TRAIL −/−, p=0.005). Immunohistochemical analysis showed induction of TRAIL in bleomycin-treated wild-type mice. Patients with IPF demonstrated lower levels of TRAIL expression than in control lung biopsies and their serum levels of TRAIL were significantly lower compared with matched controls (38.1±9.6 controls vs 32.3±7.2 pg/ml patients with IPF, p=0.002). Conclusion: These data suggest TRAIL may exert beneficial, anti-inflammatory actions in chronic pulmonary inflammation in murine models and that these mechanisms may be compromised in human IPF.